Evaluation the Level of Human Epididymal Protein 4 (HE4) in Patients of Suspicious Ovarian Mass with Low Serum Level of Cancer Antigen 125 (CA125) - Dr. Inas A. Y. Abobaker; Mashia F.S. Bader; Prof. Dr. Ahmed M. Rizk (Aljameai, 2023)
AbstractBackground: Ovarian cancer is one of the three most common malignant tumors in the female reproductive system. Tools currently in use for differentiating between low- and high-risk patients with ovarian cancer are the tumor markers carbohydrate antigen-125 (CA-125) and the human epididymis protein 4 (HE4), as well as the index value of risk of ovarian malignancy algorithm (ROMA).Objective: to evaluate the role of the HE4 in Cases of suspicious ovarian mass with low serum level of CA125.Subject: This study included 35 patient with Ovarian mass diagnosed by clinical examination, ultrasonographical, OR/ and Radiological examination. Patient with serum level of CA125 less than 100. No history of chemotherapy or radiotherapy. No history of another malignancy.results: There was no significant association between CA125, HE4 and ROMA against pathological findings, LN affection and ascites. There was a significant relation between Family history for cancer and ovarian tumour, history of OCP.Conclusion: Tumor marker CA125 is low sensitivity and specificity than HE4 in determination of ovarian malignancy. The presence of normal serum level of CA125 does not exclude presence of ovarian malignancy. المستخلص:الخلفية: سرطان المبيض هو واحد من أكثر ثلاثة أورام خبيثة شيوعًا في الجهاز التناسلي للأنثى. الوسائل اللأنجابية المساعدة حاليًا للتمييز بيـن مرضى سـرطان المبيض منخفض وعالي الخطورة هم مستضد السرطان 125 (CA-125)  وبروتين البربخ البشري 4 (HE4) ، بالإضافة إلى قيمة مؤشر خطر الإصابة بالمبيض )خوارزمية الورم الخبيث).الهدف: تقييم دور HE4 في حالات وجود كتلة مبيض مشبوهة ذات مستوى مصل منخفض من CA125.الموضوع: تضمنت هذه الدراسة 35 مريضة مصابة بكتلة مبيض تم تشخيصها عن طريق الفحص السريري ، وفحص الموجات فوق الصوتية ، والفحص الإشعاعي. كان جميع المرضىى لديهم مستوى CA125 في الدم أقل من 100 وليس لهم تاريخ من العلاج الكيميائي أو العلاج الإشعاعي ولا يوجد تاريخ لورم خبيث آخر.النتائج: لم يكن هناك ارتباط معنوي بين مستضد السرطان 125 (CA-125)  وبروتين البربخ البشري 4 (HE4) ، بالإضافة إلى قيمة مؤشر خطر الإصابة بالمبيض ضد النتائج المرضيه. كانت هناك علاقة ذات دلالة إحصائية بين التاريخ العائلي للسرطان وأورام المبيض، وتاريخ موانع الحمل الفمويه.